Research design : qualitative, quantitative, and mixed methods approaches - Creswell, John W. (Thousand Oaks, California : SAGE, 2009)
Publisher's Description: The Third Edition of the bestselling text Research Design by John W. Creswell enables readers to compare three approaches to research-qualitative, quantitative, and mixed methods-in a single research methods text. The book presents these three approaches side by side within the context of the process of research from the beginning steps of philosophical assumptions to the writing and presenting of research. Written in a user-friendly manner, Creswell's text does not rely on technical jargon. He cuts to the core of what a reader needs to know to read and design research in part by showcasing ideas in a scaffold approach so that the reader understands ideas from the simple to the complex. Key updates to the Third Edition: Presents the preliminary steps of using philosophical assumptions in the beginning of the book; Provides an expanded discussion on ethical issues; Emphasizes new Web-based technologies for literature searches; Offers updated information about mixed methods research procedures; Contains a glossary of terms; Highlights "research tips" throughout the chapters incorporating the author's experiences over the last 35 years
1. The selection of a research design -- 2. Review of the literature -- 3. The use of theory -- 4. Writing strategies and ethical considerations -- 5. The introduction -- 6. The purpose statement -- 7. Research questions and hypothesis -- 8. Quantitative methods -- 9. Qualitative procedures -- 10. Mixed methods procedures
Includes bibliographical references (p 237-245) and indexes
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Statistical methods